Building literacies in secondary school history: The specific contribution of academic writing support - Breeze, Ruth; Gerns Jiménez-Villarejo, Pilar (E-journALL, 2019)
This paper considers the specific role and effect of academic writing support in a secondary school Content and Language Integrated Learning (CLIL) context. After discussing the potential place for academic writing support in the ongoing process of fostering disciplinary literacy, we report on an experimental study in which 45 Spanish secondary school students received a short academic writing module as part of their history course. The descriptions/explanations written in their post-tests were generally found to be more complete, with more explicit discourse markers and with better textual organization than the pre-tests. We discuss the implications of this for students’ progress towards disciplinary literacy.